Analisis Manajemen Perawatan Actuator Sebagai Safety Device Dalam Memproteksi Terjadinya Overspeed Pada Mesin Penggerak Utama Kapal - Ali Khamdilah; Kundori Kundori (Politeknik Ilmu Pelayaran Semarang, 2020)
The purpose of this paper is to analyze the causes of delay in the work response of the actuator in controlling the action on the fuel injection pump rack when the ship is sailing. An actuator is a propulsion device that is driven by a pneumatic system (compressed air system) or a hydraulic system (hydraulic oil media) in the world of control applied as a safety device for machines. The accuracy of the actuator process as a tool used in security equipment on the ship's main engine plays a very important role in keeping the main propulsion engine working in safe conditions. Against the background of the weak work response of the actuator as a fuel rack propulsion on the fuel injection pump which results in damage to the main engine due to Overspeed. The problem that will be analyzed is the number of things that make the actuator work incompatible with its function. In its use, the actuator gets a signal command from the tachometer which functions to read the engine speed, which was previously sent to the Safety System Unit (SSU) to be processed and compared with the desired value/set according to the standard manual book of the machine. The method used is to use a qualitative descriptive approach. The conclusion of this paper is the need for good maintenance in the actuator system to prevent it from failing to protect engine work, such as checking the work response in pushing, pneumatic, or hydraulic drive systems, calibrating the output value of the tachometer or the system from the Safety System Unit (SSU).